Tightening Financial Regulation: The Impact on the Credit Cycle in the USA - A. V. Podrugina (Мир новой экономики)
The credit cycle is one of the most important elements of the business cycle. Credit expansion after the crisis is one of the key ways of economic recovery. The tightening of financial regulation in response to the crisis of 2007–2008 largely slowed down the credit expansion phase and was reflected in an abnormally prolonged phase of credit contraction for the non-financial private sector. The normal course of the credit cycle was disrupted by the increased demands of Basel III and the reform of theUSAfinancial system. The credit cycle after the crisis of 2007–2008 differs from previous crises: the recovery of credit activity was slower; the volume of credit to the non-financial private sector has not recovered even now. The article presents a comparative analysis of the behaviour of credit after crises from the point of view of the duration of recovery. In this article, the author presents the results of the research of the nature of the incident called “the credit paralysis” based on Minsky’s hypothesis of financial instability and Crotty’s theory of the endogenous formation of credit standards. It is assumed that bank credit standards are set in accordance with the level of macroeconomic variables — the level of GDP, interest rates, the volume of loans taken. Using the vector autoregressive model, the author analyzed the change in credit activity in response to changes in credit standards, as well as the process of forming credit standards depending on macroeconomic indicators. Therefore, the author concluded that the excessive increase in credit standards due to the introduction of Basel III requirements in response to the crisis that violated the normal course of the credit cycle. Based on the author’s econometric study, the author built a stylized model of theUSAcredit cycle, taking into account the influence of specific factors of the crisis of 2007–2008: pre-crisis financial innovation and post-crisis tightening of financial regulation.